Features : perspectives on a key notion in linguistics - Kibort, Anna.; Corbett, Greville G. (Oxford : Oxford University Press, 2010)
This text presents a critical overview of current work on linguistic features - gender, number, case, person, etc. - and establishes new bases for their use in the study and understanding of language.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Grammar, Comparative and general